A review of hard carbon anode: Rational design and advanced characterization in potassium ion batteries. Issue 2 (2nd January 2022) - Lei, Hang; Li, Jinliang; Zhang, Xiyun; Ma, Liang; Ji, Zhong; Wang, Zilong; Pan, Likun; Tan, Shaozao; Mai, Wenjie
Abstract: K‐ion batteries (KIBs) have attracted tremendous attention and seen significant development because of their low price, high operating voltage, and properties similar to those of Li‐ion batteries. In the field of development of full batteries, exploring high‐performing and low‐cost anode materials for K‐ion storage is a crucial challenge. Owing to their excellent cost effectiveness, abundant precursors, and environmental benignancy, hard carbons (HCs) are considered promising anode materials for KIBs. As a result, researchers have devoted much effort to quantify the properties and to understand the underlying mechanisms of HC‐based anodes. In this review, we mainly introduce the electrochemical reaction mechanism of HCs in KIBs, and summarize approaches to further improve the electrochemical performance in HC‐based materials for K‐ion storage. In addition, we also highlight some advanced in situ characterization methods for understanding the evolutionary process underlying the potassiation–depotassiation process, which is essential for the directional electrochemical performance optimization of KIBs. Finally, we raise some challenges in developing smart‐structured HC anode materials for KIBs, and propose rational design principles and perspectives serving as the guidance for the targeted optimization of HC‐based KIBs. Abstract : Hard carbons are considered as a promising anode material for K‐ion batteries. This review presents the electrochemical reaction mechanism of hard carbons in K‐ion batteries, and summarize rational approaches to further improve the electrochemical performance in hard carbon‐based materials for K‐ion storage. In addition, some advanced in situ characterization methods for understanding the storage mechanism are also highlighted.